Modeling business dependencies for credit portfolios - Leippold, Markus A. (Henry Stewart Talks, 2007)
Portfolio credit risk, Integrating macrostructural and microstructural interdependencies, Gaussian copula, Credit portfolio as a graph, Impact of business dependencies on correlation, Feedback effects, Marginal risk contribution
Archived at 2022/04/04